The effect of an intermittent protocol on strength performance in female football players: an exploratory study - Pompeo,Alberto (2023)
ABSTRACT Football is a sport that involves a combination of continuous and intermittent effort. Therefore, players need to be able to recover quickly between moments of high intensity to continue to perform at a high level of output throughout the entire match. The present study aimed to evaluate the effect of an intermittent exercise protocol on the rate of high-intensive force production through the countermovement test (CMJ) in elite Portuguese female soccer players. The sample consisted of 12 players from the first division of women's football in Portugal (Age= 18.1± 0.9 years; Weight= 60.10± 5.8 Kg; Height= 1.63± 4.8 cm; BMI= 22.48± 1.5 kg/m2). The players performed an intermittent exercise protocol on a cycle ergometer, lasting 8 minutes, in which each minute corresponded to 40 seconds of high-intensity (4 W/kg, based on the player's body weight) and 20 seconds of low-intensity (75W). Before and after the protocol, the players performed the CMJ. Through the results obtained, it was possible to observe that players presented a significant decrease in the height of the CMJ between the two moments (before- 29.92± 3.55 cm vs after- 26.92± 4.05 cm; p < .01). The present study allowed us to conclude that intermittent exercise protocol promoted a negative influence on CMJ performance.